2022
DOI: 10.1149/2162-8777/ac90ec
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Spacer Dielectric Engineered Vertically Stacked Junctionless Nanosheet FET for Sub-5 nm Technology Node

Abstract: This manuscript for the first time provides insights on the impact of different spacer materials for the vertically stacked junctionless nanosheet field-effect transistor (JL-NSFET). The analog/radio-frequency (RF) performances of several single-k and dual-k spacers in two approaches namely (1) inner high-k + outer low-k and (2) inner low-k + outer high-k are explored at 3nm gate length. It is noted that the use of TiO2 spacer improves analog performance of the JL-NSFET whereas the usage of SiO2 improves the R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…This reduction in I off is probably due to the higher vertical electrical field in the off state. 46 It is also noticed that TGF reduces slightly with the increase in K BSP as picturized in Fig. 6b.…”
Section: Optimization Of Bottom Spacer Height (H Bsp ) Of Jl-bspmentioning
confidence: 63%
“…This reduction in I off is probably due to the higher vertical electrical field in the off state. 46 It is also noticed that TGF reduces slightly with the increase in K BSP as picturized in Fig. 6b.…”
Section: Optimization Of Bottom Spacer Height (H Bsp ) Of Jl-bspmentioning
confidence: 63%
“…35 is also decreased for TiO 2 spacer due to the significance increase in C gd in comparison with g ds improvement. The Gain Frequency Product 36 is an analog FOM that is used to evaluate the performance of a device. It is observed that the pronounced superiority of TiO 2 in terms of its lower f t leads to a reduction in GFP when compared to other spacers.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Introduction of spacer reduces DIBL due to shift of lateral field from gate edge towards drain, so source gets screened. 26 Comparison of analog parameters for D1 to D6.-In this subsection, the effect of analog parameters such as transconductance (g m ), output conductance (g d ), early voltage (V EA ), transconductance generation factor (TGF), and intrinsic gain (A V ) are compared for different device designs D1 to D6.…”
Section: Resultsmentioning
confidence: 99%